Lrig2 and Hpse2, mutated in urofacial syndrome, pattern nerves in the urinary bladder - Roberts, Neil A.; Hilton, Emma N.; Lopes, Filipa M.; Singh, Subir; Randles, Michael J.; Gardiner, Natalie J.; Chopra, Karl; Coletta, Riccardo; Bajwa, Zunera; Hall, Robert J.; Yue, Wyatt W.; Schaefer, Franz; et al. (Kidney international, 2019)
Mutations in leucine-rich-repeats and immunoglobulin-like-domains 2 (LRIG2) or in heparanase 2 (HPSE2) cause urofacial syndrome, a devastating autosomal recessive disease of functional bladder outlet obstruction. It has been speculated that urofacial syndrome has a neural basis, but it is unknown whether defects in urinary bladder innervation are present. We hypothesized that urofacial syndrome features a peripheral neuropathy of the bladder. Mice with homozygous targeted Lrig2 mutations had urinary defects resembling those found in urofacial syndrome. There was no anatomical blockage of the outflow tract, consistent with a functional bladder outlet obstruction. Transcriptome analysis revealed differential expression of 12 known transcripts in addition to Lrig2, including 8 with established roles in neurobiology. Mice with homozygous mutations in either Lrig2 or Hpse2 had increased nerve density within the body of the urinary bladder and decreased nerve density around the urinary outflow tract. In a sample of 155 children with chronic kidney disease and urinary symptoms, we discovered novel homozygous missense LRIG2 variants that were predicted to be pathogenic in 2 individuals with non-syndromic bladder outlet obstruction. These observations provide evidence that a peripheral neuropathy is central to the pathobiology of functional bladder outlet obstruction in urofacial syndrome, and emphasize the importance of LRIG2 and heparanase 2 for nerve patterning in the urinary tract.
Gesehen am 09.09.2019